Pengaruh Komisaris Independen, Komite Audit dan Rasio Keuangan Perusahaan Terhadap Agresivitas Pajak - Bernhard, Christopher Tannos; Veny, Veny (Owner : Riset dan Jurnal Akuntansi, 2024)
Tax Aggressiveness is the company's actions to reduce the tax burden that must be paid by the company. Every company certainly wants a smaller tax burden. The tax burden is considered by the company as a deduction from the company's profit. Tax aggressiveness in a company can be done legally or illegally and it depends on the company's decision. This study aims to examine the effect of Independent Commissioners, Audit Committee, Return on Assets, Leverage, Capital Intensity, and Company Size on Tax Aggressiveness in consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This research is a quantitative research with multiple linear regression analysis method processed using a data processing application, namely SPSS 26. The data used is secondary data obtained by library and documentation techniques. The sample selection method in this study used a purposive sampling method and obtained 24 companies with a total sample of 120 samples. Based on the research results, it can be concluded that the Independent Commissioner has a significant positive effect on tax aggressiveness and capital intensity has a significant negative effect on tax aggressiveness. While the Audit Committee, Return on Assets, Leverage, and Company Size have no significant effect on tax aggressiveness. However, if the Independent Commissioner, Audit Committee, Return on Assets, Leverage, Capital Intensity, and Company Size move simultaneously, the results will have a significant effect on Tax Aggressiveness.